A simplified checklist for the visual inspection of finished pharmaceutical products: a way to empower frontline health workers in the fight against poor-quality medicines - B. Schiavetti; E. Wynendaele; V. Melotte; J. Van der Elst; B. De Spiegeleer; R. Ravinetto (Taylor & Francis Group, 2020)
Background Substandard and falsified medicines, mainly prevalent in low and middle-income countries (LMICs), cause avoidable morbidity and mortality, and put at stake the performance of health systems. They may be prevented by an adequate implementation of pharmaceutical Quality Assurance (QA) guidelines, but unfortunately, most guidelines address upstream stakeholders and specialized staff in the supply chain. A multi-layered approach is needed, in order to empower the health workers at the point-of-care to proactively contribute to the fight against poor-quality medicines. Visual inspection is a simple technique, suitable for field screening. The findings of a survey conducted in the Democratic Republic of the Congo (DRC) suggested that it might be a fairly good (yet partial) predictor of poor-quality, when compared to full laboratory tests. Methods and results Starting from the 68-questions checklist originally used in the survey in the DRC, we developed a simplified checklist, specifically designed to guide health workers at the point of care to rapidly identify suspect poor-quality medicines. We selected those medicines' attributes the assessment of which does not require technical expertise, or access to regulatory information. Attributes were categorized according to a 3-level risk scale, to guide decision-making on suspect poor-quality medicines, based on an informed risk assessment. The simplified checklist contains 26 binary questions (YES/NO), grouped into four themes: packaging, identification, traceability, and physical appearance. Each non-conformity corresponds to a level of risk for patients. The user is guided towards three possible actions: A) reasonably safe for dispensing; B) dispense with explanation; C) quarantine and make a risk-benefit evaluation before dispensing. Conclusion The simplified checklist should now be implemented in real-life setting in LMICs. If proven useful in guiding health workers at the point-of-care to take rapid, transparent, patient-centred actions when facing a suspect poor-quality medicine, it could be further extended to address specific formulations. Digitalization for linkage with pharmacovigilance programs could also be considered.